Global patterns of mangrove resource utilization: a systematic review - Hamza, Amina Juma; Esteves, Luciana S.; Cvitanović, Marin; Kairo, James G. (Frontiers in Sustainable Resource Management, 2024)
Ecosystem services, encompassing the direct and indirect benefits of natural systems, are extensively studied in the context of mangroves. These carbon-rich ecosystems support coastal fisheries, shorelines, and harvestable resources to local communities. However, research on mangrove ecosystem services primarily are at a local scale, with limited exploration of global variations in resource utilisation. This paper aims to bridge this knowledge gap through a systematic review of the existing literature conducted in Web of Science to assess the geographical variations in the coverage of mangrove use and ecosystem services. Out of 310 papers analysed, Asia had the highest coverage (43%) with support to fisheries (39%) being the most researched ecosystem service worldwide. Direct use of mangrove resources exhibited regional variations, particularly in Asia, Africa, and North America. Mangrove wood, primarily used for fuel (16%) and construction (15%), was the most documented resource, with its usage persisting in low-income countries. Notably, a shift from being a primary income source to subsistence use was observed in Asia, Africa, and South America. Intrinsic and cultural services were less mentioned in the literature, emphasizing the need for future studies to focus on these areas to ensure culturally sensitive conservation efforts.